Menumbuhkan Kepercayaan Diri pada Anak (Broken Home) dengan Terapi Adlerian Islami - Haerunisa Haerunisa (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Self-confidence is very important and must be owned by a teenager to achieve success in the future. But the fact is that in Indonesia itself, there are still children who lack high self-confidence, especially in the school environment. However, the low self-confidence in adolescents is not only caused by school factors, it can be caused by other factors, one of which is parents. The role of parents in fostering self-confidence in children is very influential. Lack of parental attention to children can be caused by parental divorce. This study uses a literature review that synthesizes theories and concepts from various opinions about how parental divorce can cause a lack of confidence in children through the Adlerian Islamic therapy approach. Keywords: parental divorce; Confidence; Islamic Adlerian Therapy